LANGUAGE AS ART AND COMMUNICATION TOOL - Linda Wijaya; Nena Syahrani Syahaf Nasution (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
Language acquisition is essentially needed to sustain human socialization through communication towards one another. The purpose of this paper is to show that the language functioned as a universal language can literally support the continuity of human life in the work, business, and education. Society often neglects the importance of language and only regards language as a superficial subject to be studied. As the saying goes “Language is art”, needless to say, it truly proves that language is also related to literature which produces many contribution to literary works. Strong language literature is also an excellent phenomenon in human communication such as drama, poetry, and novel. Novel, a literary work that until now still in demand by literary fans, is a media that indirectly bring together the author with the reader. The author conveys his message to the reader through the novel. The findings of this research found that language plays an important role in maintaining and preserving human existence in communication. Language is a crucial element in implementing human body language. The expertise of the person in the language shows his skills and qualities.